2014
DOI: 10.4172/2155-9619.1000168
|View full text |Cite
|
Sign up to set email alerts
|

40/42Gy in 13 Fractions: A Safe Dose for the Brachial Plexus

Abstract: Aims: The use of hypo fractionated irradiation of the whole breast has regained much interest after the publication of the results of large randomized trials showing equivalent results as using standard fractionation (START A and B, randomized START pilot trials, Canadian trial). Due to the relatively low numbers of patients treated with hypofractionation to the supraclavicular ±axillary (S/A) region, the question of the brachial plexus tolerance continues to be discussed. Aim of this work was to assess the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…In addition, four studies were excluded due to lack of quantitative data (Platteaux et al., 2010; Sood et al., 2018; Thomas et al., 2015; Truong et al., 2012). Finally, 30 studies were included in the systematic review (Figure 1) (Amini et al., 2012; Basso-Ricci et al., 1980; Brunelli and Brunelli, 1985; Cai et al., 2016; Chen et al., 2012; Eblan et al., 2013; Fardin et al., 1990; Fathers et al., 2002; Forquer et al., 2009; Gosk et al., 2007; Hoeller et al., 2004; Johansson et al., 2000; Kıbıcı et al., 2020; Killer and Hess, 1990; Ko et al., 2011; Kori et al., 1981; LeQuang, 1989; Lindberg et al., 2019; Merle et al., 1988; Metcalfe and Etiz, 2016; Mondrup et al., 1990; Morse et al., 2022; Narakas, 1984; Pierce et al., 1992; Powell et al., 1990; Studer et al., 2014; Teixeira et al., 2007; Warade et al., 2019; Wu et al., 2014; Yin et al., 2023). Figure 2 shows the distribution of the included studies based on the publication year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, four studies were excluded due to lack of quantitative data (Platteaux et al., 2010; Sood et al., 2018; Thomas et al., 2015; Truong et al., 2012). Finally, 30 studies were included in the systematic review (Figure 1) (Amini et al., 2012; Basso-Ricci et al., 1980; Brunelli and Brunelli, 1985; Cai et al., 2016; Chen et al., 2012; Eblan et al., 2013; Fardin et al., 1990; Fathers et al., 2002; Forquer et al., 2009; Gosk et al., 2007; Hoeller et al., 2004; Johansson et al., 2000; Kıbıcı et al., 2020; Killer and Hess, 1990; Ko et al., 2011; Kori et al., 1981; LeQuang, 1989; Lindberg et al., 2019; Merle et al., 1988; Metcalfe and Etiz, 2016; Mondrup et al., 1990; Morse et al., 2022; Narakas, 1984; Pierce et al., 1992; Powell et al., 1990; Studer et al., 2014; Teixeira et al., 2007; Warade et al., 2019; Wu et al., 2014; Yin et al., 2023). Figure 2 shows the distribution of the included studies based on the publication year.…”
Section: Resultsmentioning
confidence: 99%
“…This review showed that radiation-induced injuries typically involve the entire BP, which often results in patients experiencing pain as well as motor and sensory deficits at all levels of the BP. There is considerable variability in the time between radiation exposure and the onset of clinical symptoms, a range of 5.8–540 months, with an average span of 33 months (Lindberg et al., 2019; Studer et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Hypofractctionation >2.11 Gy/f may result in a higher risk for RICNP due to hot spots. RT-induced nerve damage is known for a potentially long latency till clinical appearance (19).…”
Section: Discussionmentioning
confidence: 99%
“…show the collection of clinical data for brachial plexus. The SBRT data are obtained from(Forquer et al 2009, Benedict et al 2010, Emami 2013, Sood et al 2018, Timmerman 2022, HFRT data from(Stoll and Andrews 1966, Svensson et al 1975, Salner et al 1981, Barr and Kissin 1987, Powell et al 1990, Miller et al 1998, Johansson et al 2002, Bajrovic et al 2004, Studer 2014, Timmerman 2022 and CFRT data are obtained from the following (Basso-Ricci et al 1980, Powell et al 1990, Amini et al 2012, Truong et al 2012, Eblan et al 2013, Emami 2013, Chen et al 2014, Lundstedt et al 2015, Thomas et al 2015, Metcalfe and Etiz 2016, Yahya et al 2016, Yang et al 2016, Yathiraj et al 2016, Timmerman 2022). Some of the selected clinical data above are also available in Yan et al (2019) (see table 2A and table 2B in Yan et al (2019)).…”
mentioning
confidence: 99%